Seroprevalence and burden of hepatitis E viral infection among pregnant women in central Nigeria attending antenatal clinic at a Federal Medical Centre in Central Nigeria - Ehi Airiohuodion, Philomena; Wartel, Anh; Yako, Andrew B.; Mac, Peter Asaga (Frontiers in Medicine, 2022)
Abstract Introduction HEV infection may be life-threatening in pregnant women and has been linked with 20-30% mortality, especially in the third trimester of pregnancy. HEV infection leads to elevated levels of preterm labour and other immunological parameters. It is vertically transmitted and could lead to poor feto-maternal outcomes. especially in fulminating viral hepatitis where both the mother and foetus could be lost. There is currently no known treatment or vaccine for HEV. There is therefore a need to study HEV seroprevalence and burden among vulnerable groups, such as pregnant women and their newborns in Nigeria, where maternal mortality is highly significant. Methods A total of 200 samples were collected from pregnant women attending antenatal clinic at the Federal Medical Centre (FMC) Keffi in central Nigeria, of which 156/200 samples were from HIV-negative pregnant women and 44/200 were from HIV-positive pregnant women, using a simple random sampling method. Results In total, 200 pregnant women [78.0% (156/200) HIV-negative pregnant women and 22.0% (44/200) HIV-positive pregnant women] were recruited for this study. The ages of the pregnant women ranged from 15-49 years, with a mean age of 26.4 years (±6.23). The overall HEV IgG seropositivity in the study population was 31.5% (63/200); 95% CI (30-33). Conclusion This study highlighted an unexpectedly high seroprevalence of HEV and poor feto-maternal outcomes in pregnant women residing in a rural and urban setting of central Nigeria. The study showed that the inherently high HEV seropositivity and poor feto-maternal outcomes may not be attributed to HEV viral hepatitis only but may be a combination of extrinsic and intrinsic factors. Key words: HEV, Fetomaternal Outcome, IgG, Nigeria, Fulminant Hepatitis.